Avaliação da capacidade antioxidante e estudo eletroquímico do extrato hidroalcoólico da Commelina erecta L. - GONÇALVES, Jhonilson Pereira (2021)
Weeds are still poorly studied with regard to their medicinal properties. In view of this, the present work evaluated the total antioxidant potential of the hydroalcoholic extract of Commelina erecta L. using spectrophotometric and electrochemical techniques. The chemical characterization of the species was obtained by Mass Spectrometry (MS / MS), whose proposal of elucidation showed C-glycosylated and O-glycosylated flavonoids. The antioxidant activity was expressed by three different methods: Percentage of consumption of DPPH radical as a function of 0.0625 concentrations; 0.125; 0.25; 0.5 and 1.0 mg/mL, whose response was 54.3% reduction for the maximum EBCE concentration; Calculation of the IC50 by means of linear regression adjustment, where the IC50 was obtained: 0.07 ± 1.21 (mg/mL); And calculation of the electrochemical index (IE) obtained through the electrochemical techniques of Square Wave Voltammetry (SWV) and Cyclic Voltammetry (CV). The answer for both techniques was IE: 10.73 ± 2.72 and 2.87 ± 0.52, respectively. These results were compared with the routine IE: 7.24 ± 0.36 (SWV) and 3.51 ± 0.42 (CV), which showed C. erecta as a good candidate for the extraction of antioxidant substances when compared to the standard routine validated by the same method. Therefore, C. erecta can be highlighted as a significant source of flavonoids and other polyphenols of great relevance in the chemical / pharmacological area.